THE INFLUENCE OF PROBLEM-BASED LEARNING AND CREATIVE THINKING ABILITY ON SCIENTIFIC LITERACY OF FOURTH GRADE STUDENTS AT SDN 137 CIJEROKASO, BANDUNG CITY - Resniawati Kurnia; Maman Rumanta; Isti Rokhiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The importance of developing science literacy in elementary schools to increase the student’s problem solving abilities. By strenghtening science literacy, students are better to understand complex concepts an apply logical reasoning to fine efective solutions. This research made is to analyze the influence of PBL on science literacy skills, creative thingking skills on science literacy competence, and the interaction between PBL, creative thingking skills dan science literacy. This research involved fourth grade students from SDN 137 Cijerokaso Kota Bandung, divided into a experimental and control group. Using a quasi-experimental research design, an instrument to get a creativity is a open-ended task while science literacy was measured using mulyiple choice test. Two-way ANOVA results showed that PBL alone did not significantly affect science literacy skills (sig = 0.726). However, creative thingking skills had a significant impact (sig = 0.008), and there was a significant interaction effect between PBL and creative thingking skills on science literacy (sig = 0.021). These findings indicate that while PBL by itself may not directly enhance science literacy, its combination with student creative thingking skills contributes meaningfully to improving students’ science literacy skills.